Stunting disparities and its associated factors among preschool children of employed and unemployed mothers in Gondar City: a comparative community-based cross-sectional study - Tekeba, Berhan; Tarekegn, Bethelihem Tigabu; Zegeye, Alebachew Ferede; Ayele, Amare Demsie (Frontiers in Nutrition, 2023)
Introduction: A stunted is too short for his or her age, which is the most common cause of morbidity and mortality in children under five in developing countries. Stunting in preschool children is caused by a multitude of socioeconomic and child-related factors, including the employment status of women. This study aimed to compare the prevalence and factors associated with stunting of preschool children among employed and unemployed mothers in Gondar city, Northwest Ethiopia, in 2021. Methods: Community-based comparative cross-sectional study was conducted among 770 preschool children of employed and unemployed mothers in Gondar city. A structured questionnaire-based interview with anthropometric measurements was used to collect data. A multi-stage sampling technique was used. Data were entered into EPI Info version 7.22 and transferred to Stata version 14 for further analysis. To identify factors associated with stunting, a binary logistic regression analysis was used. The presence of an association was declared based on a p-value of <0.05 and confidence intervals. Results: A total of 770 preschool children participated in the study. The overall prevalence of stunting among preschool children was 39.7% (95% CI: 36.3-43.2). The prevalence was higher among preschool children of employed mothers (42.6%) (95% CI: 37.6-47.5) than among unemployed mothers (36.7%) (95% CI: 32.0-41.7). Maternal age and wealth status were significantly associated with stunting among unemployed mothers, while family size, number of under-five children, and having a home servant were associated with stunting of preschool children among employed mothers. Stunting is more common in preschool children of employed mothers than in those of unemployed mothers. As a result, intervention such as awareness creation for employed mothers to devote time and care to their children is required, as well as concerned bodies providing assistance to women having preschool children is required, The nutrition intervention should focus on encouraging dietary diversity to combat the existing nutrition-associated stunting in children. Likewise, further research work on the difference between employed and unemployed mothers' child stunting status and investigating extra variables like the number of hours worked by an employed mother is also recommended to upcoming researchers.